Дослідження впливу високовольтного електричного поля на біологічну продуктивність насіння соняшнику - Стьопін, Юрій Олексійович; Степин, Юрий Алексеевич; Stopin, Yurii; Гулевський, Вадим Борисович; Гулевский, Вадим Борисович; Hulevskyi, Vadym; Борохов, Іван Валерійович; Борохов, Иван Валерьевич; Borokhov, Ivan (My University, 2019)
UK: Робота присвячена питанням передпосівної обробки насіння соняшнику постійно не однорідним електричним полем високої напруги. Розроблено структурну та електрична схеми експериментальної установки. Наведено результати обробки електричним полем високої напруги насіння соняшнику. Побудовано графічні залежності. RU: Работа посвящена вопросам предпосевной обработке семян подсолнуха постоянным не однородным электрическим полем высокого напряжения. Разработана структурная и электрическая схемы экспериментальной установки. Приведены результаты обработки электрическим полем высокого напряжения семян подсолнуха. Построены графические зависимости. EN: The efficiency of crop production depends to a large extent on the quality of the seed. The results of years of scientific research and production testing show that physical factors and, first and foremost, electric and magnetic fields can be used to achieve this. This paper analyzes recent research in the field of processing the influence of high-voltage electric field on biological productivity of seed material. To prove the positive effect of high-voltage electric field on seed growth of cultivated plants, an experimental setup was developed. Sunflower seeds are to be treated with a constant, non-homogeneous, high voltage electric field. The purpose of the study is to experimentally confirm the positive effect of the electric direct high-voltage DC field on the speed and degree of germination of plant seeds. The article presents a block diagram and a schematic diagram of the electrical experimental setup. The design of the radiation chamber is presented. The technique of conducting a seed treatment experiment with an electromagnetic field is described. The duration of irradiation of sunflower seeds was: the first group - ten minutes; the second group - twenty minutes. The results of the experiment are given. Graphical dependences of the temperature of heating of sunflower seeds on the energy received by him were constructed. Seeds of the first, second group and untreated seeds were planted. A land plot of 2.4 × 5 m was allocated for planting of each group.
Исследование влияния высоковольтного электрического поля на биологическую продуктивность семян подсолнуха
Investigation of the effect of high-voltage electric field on biological productivity of sunflower seeds
Keywords: електромагнітна обробка; схожість; напруженість електромагнітного поля; тривалість обробки; електричне поле високої напруги; электромагнитная обработка; всхожесть; напряжённость электромагнитного поля; длительность обработки; электрическое поле высокого напряжения; electromagnetic processing; germination; intensity of the electromagnetic field; duration of treatment; electric field of high-voltage